Social media and its legal basis - Muhannad Habib , Rese; Hamidreza Shariatmadari, Dr.; Jabbar ajkhim Tamim, Asst. Prof. Dr. (lark, 2025)
The research focused on the nature of social media platforms and their definition as digital spaces and virtual environments that allow users to create and share content and interact with others through various media forms that are published on the platforms. The research also addressed the history of the emergence of social media sites and how they developed to reach their current form, where they have had major and decisive effects on the global scene and its political, economic, financial and social paths. The research also focused on the most important topic in social media sites, which is the legal aspect related to Article 230 of the US Communications Decency Act in the United States, which granted platforms legal protection from any accountability against them due to the posts that users upload on them that may cause serious problems for the individual, society and countries.